Sealing push ring component - THE INVENTOR HAS WAIVED THE RIGHT TO BE MENTIONED (2010)
The utility model provides a sealing push ring component serving as an important element of a build-in distributor component of a bearing support, and is mounted in front and behind the build-in distributor. The sealing push ring component comprises a sleeve, an O-shaped ring and a sealing push ring, wherein, the sleeve adopts a carbon-steel seamless steel pipe 20; a step with a certain depth is processed at the end part of the sleeve; the length of the sleeve is subject to the structure of a bearing support; the O-shaped ring is made of rubber, and can be made into different models according to actual requirements; the sealing push ring is made of nylon; two grooves in which the O-shaped ring is mounted are formed at the head of the sealing push ring; the two grooves adopt a preparation groove and a working groove; and the inner hole of the sealing push ring is processed into a threaded structure, so as to facilitate installation and disassembly. When the sealing push ring component is mounted, the O-shaped